2011
DOI: 10.1007/s10384-011-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between macular ganglion cell complex parameters and visual field parameters after tumor resection in chiasmal compression

Abstract: Examining the macular GCC was useful for evaluating structural damage in patients with chiasmal compression. Preoperative GCC parameters, especially FLV, may be useful in predicting visual function following surgical decompression of chiasmal compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 18 publications
7
32
1
5
Order By: Relevance
“…Monteiro et al (9) described hemianopic full-thickness macular thinning in patients with chiasmal compression. Others reported inner retinal thickness (combined RNFL, ganglion cell layer, and inner plexiform layer) thinning with similar results (7,8), and a more recent study showed preferential ganglion cell loss in the nasal hemirentina in patients with pituitary tumors (16). …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Monteiro et al (9) described hemianopic full-thickness macular thinning in patients with chiasmal compression. Others reported inner retinal thickness (combined RNFL, ganglion cell layer, and inner plexiform layer) thinning with similar results (7,8), and a more recent study showed preferential ganglion cell loss in the nasal hemirentina in patients with pituitary tumors (16). …”
Section: Discussionmentioning
confidence: 52%
“…Some reports indicate that postoperative improvement in VF occurs with preserved RNFL or preserved inner retinal thickness (RNFL, ganglion cell layer, and inner plexiform layer) (79,17) An additional report described nasal thinning of the inner retinal layers postoperatively (8). In our study, 93% of eyes had nasal GCC loss postoperatively and 87% experienced VF improvement postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Ohkubo et al [ 55 ] evaluated the relationship between macular GCL and VF parameters in chiasmal compression and the potential for GCL parameters in order to predict the short-term post-surgical VF. Examining the macular GCL was useful for evaluating structural damage in patients with chiasmal compression.…”
Section: Compressive Chiasmal Diseasesmentioning
confidence: 99%
“…Chiasmal compression from pituitary tumours can result in retrograde degeneration of the ganglion cell axons and thinning of the nasal and temporal retinal nerve fibre layer, [41][42][43][44][45][46][47][48] for which ganglion cell complex analysis can provide more sensitive measurements. 49 Future advances in optical coherence tomography technology will allow further improvements in the detection and quantification of optic nerve dysfunction and subtle changes in nerve head morphology resulting from ocular tumours.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%